Secure IT systems : 24th Nordic Conference, NordSec 2019, Aalborg, Denmark, November 18-20, 2019, Proceedings /: 24th Nordic Conference, NordSec 2019, Aalborg, Denmark, November 18-20, 2019, Proceedings. (2019) - Unknown
No abstract available